Second Life of Post-Mining Facilities: Mines as a Tourist Attraction of Southern Poland - Hojka, Zbigniew (Studia Historiae Oeconomicae, 2023)
The aim of this article is to present a tourist mining path located in southern Poland. This involves coal, silver, gold, salt, flint, chalk, uranium mines and oil wells. It includes some buildings connected with workers and mine-owners as well. These buildings were previously tied to mining. Currently, they function as museums or service-buildings.